Tree and Stand Aerial Volume Tables for Sal (Shorea robusta) - Tiwari, K. P.; Parthasarthy, V. (Indian Forester, 1979)
Tree and Stand aerial volume tables for Sal (Sharea robusta) were prepared on 1:10,000 Panchromatic aerial photographs of Timli Block in Doon Valley covering an area of nearly 5000 ha. Data for 153 trees for tree aerial volume table and 51 plots for stand aerial volume table was collected from aerial photographs as well as from the ground. For Tree aerial volume table an array of independent variables namely photo tree height, photo crown diameter, ground height and ground dbla along with their transformation were tested with tree volume as dependent variable. It was Found that Photo height2 X Photo crown diameter eplained 51.95% of variation in tree volume with a standard error of estimate of 58.6%. Similarly for stand aerial volume table photo stand height, Average crown diameter, Crown closure percent, crown count along with their ground counterpart and transformations were tested against the dependent variable stand volume. It was found that a combination of photo height, crown clsure, average crown diameter, explained 49% of variation in stand volume with the standard error of estimate of 25.72%. The usefulness of aerial volume tables in the context of forest inventory have been highlighted.